2019
DOI: 10.3390/f10040356
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Leaf Carbon Isotope in Plants in Different Lithological Habitats in a Karst Area

Abstract: Drought is the major factor that limits vegetation recovery in rocky desertification areas. The leaf carbon isotope (δ13C) value is related to plant water-use efficiency (WUE) and is of great significance in revealing the WUE characteristics of species in karst areas. Measurements of the δ13C value in plant leaves and the nutrient and water contents of lithologic soils were obtained for six woody species (cypress, Cupressus funebris Endl.; mansur shrub, Coriaria nepalensis Wall.; camphor, Cinnamomum bodinieri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Foliar δ l3 C not only offers a comprehensive insight into how plant species interplay with and respond to their biotic and abiotic environments but also reveals the resource acquisition strategies of plant species throughout the growth period (Cao et al., 2020; Fu et al., 2020; Ma et al., 2018). In addition, previous studies on the water use efficiency (WUE) of plant species have reported that foliar δ l3 C is the best option for quantifying the WUE of plant species due to its advantages of high precision and low destructiveness (Bush et al., 2017; Marhaba et al., 2020; Zou et al., 2019). In recent decades, several studies have been conducted on the response of plant δ l3 C to climate variables (Gatica et al., 2017; Liu et al., 2015; Sun et al., 2018), soil variables (Liu et al., 2020; Ogaya & Peñuelas, 2008; Verlinden et al., 2015), and habitat conditions (Song et al., 2019; Zou et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foliar δ l3 C not only offers a comprehensive insight into how plant species interplay with and respond to their biotic and abiotic environments but also reveals the resource acquisition strategies of plant species throughout the growth period (Cao et al., 2020; Fu et al., 2020; Ma et al., 2018). In addition, previous studies on the water use efficiency (WUE) of plant species have reported that foliar δ l3 C is the best option for quantifying the WUE of plant species due to its advantages of high precision and low destructiveness (Bush et al., 2017; Marhaba et al., 2020; Zou et al., 2019). In recent decades, several studies have been conducted on the response of plant δ l3 C to climate variables (Gatica et al., 2017; Liu et al., 2015; Sun et al., 2018), soil variables (Liu et al., 2020; Ogaya & Peñuelas, 2008; Verlinden et al., 2015), and habitat conditions (Song et al., 2019; Zou et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies on the water use efficiency (WUE) of plant species have reported that foliar δ l3 C is the best option for quantifying the WUE of plant species due to its advantages of high precision and low destructiveness (Bush et al., 2017; Marhaba et al., 2020; Zou et al., 2019). In recent decades, several studies have been conducted on the response of plant δ l3 C to climate variables (Gatica et al., 2017; Liu et al., 2015; Sun et al., 2018), soil variables (Liu et al., 2020; Ogaya & Peñuelas, 2008; Verlinden et al., 2015), and habitat conditions (Song et al., 2019; Zou et al., 2019). Although few attempts have taken an interest in WUE of desert riparian forests in Tarim and Heihe River basins in arid regions of northwestern China, the studies have only taken into account single plant types or unique age structure (Ren et al., 2014; Si et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The annual average temperature is 18.4 ℃, with the highest and lowest temperatures of 32.4 ℃ and 6.6 ℃ respectively. It is warm and dry in winter and spring, humid and hot in summer and autumn; (3) rocky deserti cation: the soil is mainly limestone and marl, and the exposed area of bedrock is more than 70% (Zou et al 2019). The main vegetation is subtropical evergreen deciduous coniferous broad-leaved mixed forest; as an economic species, Zanthoxylum planispinum var.…”
Section: Methodsmentioning
confidence: 99%
“…Such large intraspecific variation has been attributed to increase in species' water-use efficiency with increasing elevation and its inherent adaptive plasticity to variable environmental conditions (Cordell et al, 1998;Peri et al, 2012). Studies have also reported variation in foliar δ 13 C with other environmental attributes such as precipitation, soil nutrients, solar radiation, and VPD (Vitousek et al, 1990;Chen et al, 2017;Zou et al, 2019;Bauman et al, 2022a). Variation in foliar δ 13 C with elevation can also result from the influence of leaf morphology (leaf thickness or LMA, for example), which leads to longer diffusion pathways for CO 2 into the leaf and decreases the internal-to-ambient CO 2 concentration ratio (c i /c a ) and hence causes enrichment of foliar δ 13 C in montane flora (Körner et al, 1986;Prentice et al, 2014).…”
Section: Foliar δ 13 C and Elevationmentioning
confidence: 99%